The Impact of Gamification Learning on Student Motivation in Elementary School Learning - Baso Intang Sappaile (Scientechno: Journal of Science and Technology, 2024)
Lately, many students have found a lack of motivation in learning in elementary schools. This can be caused by a lack of methods or use of technology that can attract students' attention so they are motivated to learn. Student motivation is a key factor in successful learning in elementary schools. However, one often finds it challenging to maintain high levels of motivation among students. For this reason, a gamification approach, which uses game elements in learning, has attracted attention as a way to increase student motivation. This research aims to determine the impact of gamified learning on student motivation in learning in elementary schools. The focus is to find out whether the use of game elements in learning can increase student motivation. This research uses a quantitative approach with a preposttest-posttest experimental design. Data was collected through questionnaires that measured students' motivation levels before and after the intervention. The research results show that gamified learning has a positive impact on student motivation in elementary schools. Students who engaged in learning with gamification elements showed greater increases in their motivation levels compared to students who received conventional learning. Factors such as challenge, reward, and self-recognition in the context of play help increase student interest and engagement in learning. The conclusion of this research explains that gamified learning can be an effective tool for increasing student motivation in elementary schools. The integration of game elements such as points, levels, and challenges in learning can increase student interest, engagement, and overall motivation. These findings provide an important contribution to the development of more innovative and effective learning strategies in the future.